Transmission of multimedia content over wireless networks - part II - Pang, Zhi Hao. (2010)
The project studies a class of MIMO (multiple-input multiple output) code called Diversity embedded Space-Time Code (DE-STC). MIMO system uses multiple antennas at both the transmitter and receiver. It offers high spectral efficiency (i.e. increase in data throughput) and link diversity (i.e. increase in link reliability) without additional bandwidth. Here, the DE-STCs are used to investigate its suitably in layered video transmission, specifically the H.264 SVC video, over the wireless networks. SVC video contains different video layers, some with higher importance (i.e. base layer) than others (i.e. enhancement layers). DE-STCs attempt to transmit the important video layer with higher diversity gain, and the less-important video layer with lower diversity gain. MATLAB simulations (i.e. simulating transmission of multimedia data over wireless channel) are performed to demonstrate the capabilities and advantages of DE-STCs over a regular space-time code that only employs a single diversity level. The single diversity level code used here is the Quasi-Orthogonal Space-Time Block Code (QO-STBC). The project is divided into two parts: Part I focuses on understanding the video content bit representation (i.e. bit rate, frame size, width, etc.) which will then attempts to code the important and less-important layers to the desired bit size. Therefore, Part I of the project prepares a source video file for Part II’s simulations. The work of Part I is discussed in the project titled “Transmission of Multimedia Content over Wireless Networks Part I”. Part II focuses on the simulations of wireless transmission using the DE-STCs. The important layer and less-important layer are separated in the simulation program and protected with different diversity levels provided in the DE-STCs. These layers are then reassembled to produce the simulation video outputs. Note that this report will only cover the work of Part II.